How neuroimaging can help us to visualise and quantify pain? - Wartolowska, K (Wiley, 2012)
Pain is a complex and multidimensional experience, which is subjective for an individual and modulated by physiological and psychological factors. Therefore, it is difficult to quantify pain and there are no objective pain measures available at the moment. Neuroimaging provides an objective measure of changes in brain activity related to pain perception. In this review, we demonstrate that pain-related brain activation is complex and can be best studied as a dynamic network of interconnected regions. Finally, we use the placebo and nocebo effects to discuss the factors involved in modulation of pain experience. © 2011 European Federation of International Association for the Study of Pain Chapters.